Characteristics and Genetic Mechanisms of Normal-Pressure Fractured Shale Reservoirs: A Case Study From the Wufeng–Longmaxi Formation in Southeastern Chongqing, China - Wang, Jinxi; Tan, Xianfeng; Wang, Jia; Zhang, Hualian; Zhang, Ye; Guo, Dongxin; Wang, Xiaofeng; Lei, Zhian; Zeng, Chunlin; Yao, Guanghua (Frontiers in Earth Science, 2021)
Compared with the overpressure conditions of shale reservoirs in the Jiaoshiba area, exploring the controlling factors of changes in shale reservoir physical properties under normal-pressure accumulation is of great significance to shale gas exploration. To achieve this, X-ray powder diffraction, nitrogen adsorption, and scanning electron microscopy were carried out to determine mineral content, permeability, porosity, and pore structure for well core and outcrop samples of the Wufeng–Longmaxi Formation in southeastern Chongqing, China. Field observations and drilling cores revealed abundant structural fractures in southeastern Chongqing, offering potential main storage space for shale gas. Findings also determined that high-quality source rocks are located in the lower part of the Wufeng–Longmaxi Formation, which features low porosity and low permeability, yet existing structural fractures could potentially improve permeability to a certain extent. The main factors controlling the shale reservoir with the above characteristics include the depositional environment, mineral components, total organic carbon content, and tectonic movement. The deep-water anoxic depositional environment was conducive to the complete preservation of organic matter and sedimentation of the biogenic siliceous minerals, which had a strong effect on improving the porosity of organic matter and brittleness of the rocks. The high content of quartz was found to improve rock compression resistance and brittleness, and increasing clay proportion was found to enhance the interlayer pores of clay minerals. Total organic carbon content, specific surface area, pore volume, and fracture development were all found to have direct contributions to shale gas entrapment. Overall, the most important factor resulting in normal-pressure accumulation in southeastern Chongqing was the intense tectonic movements since the Late Jurassic period which destroyed the original overpressure accumulation conditions.